Applicability of MuLBSTA scoring system as diagnostic and prognostic role in early warning of severe COVID-19. (January 2021) - Ma, Bei; Gong, Jun; Yang, Yu; Yao, Xuan; Deng, Xiaoqin; Chen, Xi
Abstract: To explore the applicability of MuLBSTA Score in COVID-19 patients, a retrospective analysis was performed on 330 cases of COVID-19 patients in Southeast Hospital of Xiaogan City, Hubei Province. The clinical characteristics of COVID-19 patients were described and multilobe infiltrate in CT, bacterial infection, lymphocyte count, smoke in history, history of hypertension, and age distribution in the population of mild and severe patients were analyzed. All included patients were scored according to the MuLBSTA early warning scoring system and its efficacy in early warning of severe symptoms was analyzed. CT feature of infiltration changes on multiple lobes, the absolute value of lymphocyte count of less than 0.8 × 10 9, accompanied by bacterial infection, history of smoking, history of hypertension, and an age of greater than 60 years old were all statistically significant factors in patients with severe COVID-19. ROC curve analysis indicated that the sensitivity, specificity and accuracy of the early warning system were 0.651, 0.954 and 0.93, respectively. The MuLBSTA Score has a good early warning effect on severe COVID-19 patients. Highlights: This study explores the applicability of MuLBSTA Score in COVID-19 patients. COVID-19 patients were scored according to the MuLBSTA early warning scoring system. Infiltration changes on multiple lobes was statistically significant factors in COVID-19 patients. Sensitivity, specificity and accuracy of the early warning system were 0.651, 0.954 and 0.93, respectively.